FORECASTING OF PROCESSES THE TURNOVER AND STRUCTURE OF THE FINANCIAL RESOURCES OF THE BANKING SECTOR - Narimanov Baxodir Absalomovich (Journals Park Publishing, 2022)
The purpose of the article is to develop a two-tier model and methodology for forecasting indicators of agricultural development and the territorial distribution of interrelated production of the agro-industrial complex of the region. The developed models take into account both the economic and social parameters of the functioning of the AIC. Alternative options are proposed and structural changes are justified in the production of agricultural products, processing enterprises in the conditions of increasing social orientation of the development of the agrarian economy.
Keywords: Structural Changes; Economic Management; Agro-Industrial Complex